2021
DOI: 10.1002/aepp.13204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contract farming on diets and nutrition in Ghana

Abstract: Contract farming gained importance in many developing countries. While effects of contracting on smallholder farmers' incomes were analyzed in previous studies, diet and nutrition effects are not yet well understood. Here, we examine the effects of contract farming on dietary diversity and child anthropometrics, using survey data from the palm oil sector in Ghana. Contracting improves smallholder nutrition, but the effects vary by contract type. We distinguish between marketing contracts and resource‐providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…However, NCFA farmers have more access to off-farm income than CFA farmers, which is also expected. These results are in line with Debela et al [ 29 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, NCFA farmers have more access to off-farm income than CFA farmers, which is also expected. These results are in line with Debela et al [ 29 ].…”
Section: Resultssupporting
confidence: 94%
“…Mishra et al [ 13 ] found that CFA provided high quality inputs, which incentivises most farmers to participate in CFA. Debela et al [ 29 ] finds CFA improving nutrition among oil palm farmers, and tobacco production under CFA as more efficient.…”
Section: Contract Farming Arrangement In Zimbabwementioning
confidence: 99%
“…A growing number of studies have investigated various factors driving overall household nutrition intake and dietary diversity. These include, for example, women’s employment (Larson et al 2019 ; Rao et al 2019 ; Kassie et al 2020 ; Nikiema and Sakurai 2021 ), adoption of information and communication technologies (ICTs) (e.g., Internet use, mobile phone use) (Parlasca et al 2020 ; Ankrah Twumasi et al 2021 ), adoption of climate-smart agricultural practices (Shahzad and Abdulai 2020 ; Issahaku and Abdulai 2020 ), non-farm income (Pritchard et al 2019 ; Rahman and Mishra 2020 ), access to credit (Islam et al 2016 ; Annim and Frempong 2018 ), agricultural commercialization (Loos and Zeller 2014 ), contract farming (Debela et al 2022 ), and production diversification (Jones et al 2014 ; Dillon et al 2015 ; Ecker 2018 ; Sibhatu and Qaim 2018 ; Ayenew et al 2018 ; Chegere and Stage 2020 ; Aweke et al 2020 ). Rural households usually diversify their diets through diversifying crops and livestock in agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Contract farming, agricultural extension systems, and primary health care are proven to improve smallholder nutrition. Debela et al found that contract farming improves household- and individual-level diets and nutrition; the effects vary depending on the contract type [ 81 ]. Redesigning agricultural extension systems to increase nutrition promotion knowledge might help to improve the nutrition of smallholder farmers.…”
Section: Incentivizing Smallholders To Improve Nutritionmentioning
confidence: 99%